Decision of adjuvant chemotherapy in intermediate risk luminal breast cancer patients: A prospective multicenter trial assessing the clinical and psychological impact of EndoPredict® (EpClin) use (UCBG 2–14). (February 2020) - Penault-Llorca, Frédérique; Kwiatkowski, Fabrice; Arnaud, Antoine; Levy, Christelle; Leheurteur, Marianne; Uwer, Lionel; Derbel, Olfa; Le Rol, Annick; Jacquin, Jean-Philippe; Jouannaud, Christelle; Quenel-Tueux, Nathalie; Girre, Véronique; et al.
Abstract: Purpose: Genomic tests can identify ER-positive HER2-negative localized breast cancer patients who may not benefit from adjuvant chemotherapy. Such tests seem especially interesting in "intermediate" clinico-pathological risk categories. The psychological impact of the decision uncertainty in these women remains largely unexplored. We assessed the clinical and psychological impact of EndoPredict® (EpClin), a clinico-genomic test, in these patients. Methods: This multicenter, single arm prospective study (NCT02773004) enrolled patients for which adjuvant chemotherapy was uncertain, based on predefined criteria. The primary endpoint was the proportion of change between initial adjuvant decision and final administration of chemotherapy. Secondary endpoints included post-test (Day 17) and 1-year patient reported outcomes. Results: One third of 200 evaluable patients had a high EpClin score (≥3.32867; 10 years cumulative risk of distance failure ≥10%). The overall change rate of chemotherapy decision was 72/200 (35.8%, 95% CI 29.2–42.4). Chemotherapy was withdrawn in 57 cases (28.4% [22.2–34.8]) and added in 15 (7.5% [3.8–11.2]. 6 changes (8%) were based on patients' decisions. Anxiety and distress levels increased at Day 17 when adding chemotherapy after the test result (p < 10 −7 and 0.00022 respectively), while stable in other situations. At 1-year, all patients had returned to the baseline anxiety and distress levels (mean anxiety 51.5, +/− SD = 2.5 [max. 80], mean distress 3±1 [max. 10]). Conclusions: EndoPredict ® (EpClin) is clinically useful in deciding whether or not to administer adjuvant chemotherapy in patients with intermediate risk. A single-step decision is preferable since adding chemotherapy at a later stage increases anxiety and distress. Highlights: EndoPredict ® (EpClin) allowed a chemotherapy decision modification in 35% of the patients included in the Adendom trial. Patient-physician concertation is important: 8% of treatment changes are based on patients' will. A single-step decision including the test appears preferable to limit anxiety and distress.